The Process of Making Motion Video Tutorials Graphic by Using Adobe Premiere CC 2015 - Dzulkarnain; Evy Purwitasari, Maria; Asfirawati halik, Sri (ASIAN PUBLISHER, 2023)
In the pre-production stage, the writer looked for references from friends, the internet and others. Then the writer collects these references to be used as an idea for making motion graphics that the writer makes. The author prepares everything for motion graphic production activities such as making ideas, storyboards, photos and so on. duction stage, the writer looked for references from friends, the internet and others. Then the writer collects these references to be used as an idea for making motion graphics that the writer makes. The author prepares everything for motion graphic production activities such as making ideas, storyboards, photos and so on.